Antimicrobial photodynamic therapy in the treatment of periodontal diseases - Garcia, Valdir Gouveia [UNESP]; Theodoro, Letícia Helena [UNESP] (My University, 2015)
The colonization of the tooth surface and epithelial cells in the interior of the gingival sulcus or periodontal pocket by bacterial biofilms is a complex process that occurs even following adequate oral hygiene. The mechanical control of bacterial biofilms and deposits mineralized on the root surface is the most widely used control method (gold standard) for periodontitis. In addition, antimicrobial photodynamic therapy (aPDT) may be very useful for patients exhibiting modifying systemic factors that are capable of altering the biological response of the periodontal tissues during the tissue repair process following conventional treatment, or even influencing the progression of the disease. The clinical application of aPDT as an adjuvant for nonsurgical periodontal disease therapy begins with the irrigation of the periodontal pockets with the photosensitizing drug; after 1 minute, the irradiation of these pockets is performed with a low power.
Keywords: Antimicrobial photodynamic therapy (aPDT); Bacterial biofilms; Low power laser; Periodontitis